Governing the reformed university - Ejersbo, Niels; Greve, Carsten; Pihl-Thingvad, Signe (New York, NY Routledge, 2020)
Universities are important public institutions and are seen as key drivers for a country's economic and intellectual development. Their ability to deliver relevant research and education at the highest level have an impact on growth and progress in society, and governments attempt to control and govern the development of the universities. It is no longer left to the individual researcher or the institution to determine the role of the university.

Universities have traditionally had a special role in society with a high degree of autonomy and independence. They have been described as a self-governing Republic of Science and their internal organization is characterized as "academic tribes". However, universities can also be viewed as institutions with somewhat similar characteristics as other public institutions with highly professionalized staff.

Governing the Reformed University is a coherent volume based on a unique data set. The aim of the book is to quantitatively and qualitatively understand and explain how reforms and management instruments are implemented and how it influences different levels of the organization from the top management level to the employees within universities. It contributes to the knowledge of reform and reform impact in higher education. It also adds to our understanding of management and governance at universities and through which mechanisms management works at universities.

This book builds on and adds to the knowledge of studies of reform and governance at universities. The data used in the book consists of a number of data sets and is collected as part of a comprehensive research project. Academics and policy makers alike in the fields of public administration, public management, public policy, educational studies and accountancy will find this of high interest.
1 Introduction -- 2 Data and methods / Niels Ejersbo, Pernille Bak Pedersen, and Signe Pihl-Thingvad -- 3 University management and reforms in context - the relationship between university reforms and general reforms in the public sector / Carsten Greve & Niels Ejersbo -- 4 Controlling autonomy: governmental regulation of Danish Universities from 1989 to 2015 / Pernille Bak Pedersen -- 5 Board influence and interaction with the university management / Niels Ejersbo & Carsten Greve -- 6 Department chairs - modern managers or old administrators? / Niels Ejersbo & Carsten Greve -- 7 Autonomy and performance at universities / Niels Ejersbo, Signe Pihl-Thingvad and Maiken K. Westergaard -- 8 Academics and performance systems / Poul Erik Mouritzen, and Niels Opstrup -- 9 Modern management and working conditions in academia / Signe Pihl-Thingvad & Niels Opstrup -- 10 Conclusion / Niels Ejersbo, Carsten Greve and Signe Pihl-Thingvad.
Includes bibliographical references and index.
Keywords: Educational change; Public administration; Universities and colleges -- Administration